Strategies for Supporting Students Diagnosed with Autism Spectrum Disorders in STEM Education - Moody, Amelia K.; Kubasko, Dennis S.; Walker, Allison R. (Journal of the American Academy of Special Education Professionals, 2018)
Educators and employers are working together to promote students diagnosed with autism by developing skills related to the STEM fields. Students diagnosed with autism spectrum disorders (ASD) are showing high levels of interest in STEM fields. This paper will review STEM and ASD literature and offer methods for improving student access to education through transition services and using a Universal Design for Learning (UDL) framework in efforts to encourage a blend of evidence-based instructional methods and supports for STEM educators working to include students diagnosed with ASD in their classrooms.